Influence of Typing Master, Learning Motivation, and Peer Influence on Keyboarding Skills of Office Administration Students 2020 at UNNES - Khanza, Devita; Tusyanah, Tusyanah (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2025)
Phenomenon/Issue: Keyboarding is a key competency that students of Office Administration Education must possess. However, based on the results of typing tests, many students struggle to type using the ten-finger technique. Purpose: The purpose of this study is to analyze the influence of the Typing Master media, learning motivation, and peer influence on the keyboarding skills of 6th semester Office Administration Education students. Novelty: This research presents novelty by combining internal, technological, and social aspects in a post-pandemic context, providing a new perspective on learning office skills. Research Methods: This study uses a quantitative research approach. The sampling technique used is total sampling, meaning the entire population was used as the research sample. Data collection was conducted through observation, questionnaires, and typing tests. Data were analyzed using descriptive statistics and multiple linear regression with SPSS Statistics 28 software. Results: The results show that the usage of typing master has a positive and significant effect on keyboarding skills by 39.69%. Learning motivation also has a positive and significant impact at 65.28%. Peer influence has no significant effect. Together, typing master, learning motivation, and peer influence have a collective effect on keyboarding skills, as shown by a simultaneous determination coefficient of 66%. Research Contributions: This study contributes to several parties. For students, it raises awareness of the importance of motivation, learning media, and peer support in improving typing skills. For future researchers, it offers a reference for further studies.